The adaptor protein PID1 regulates receptor-dependent endocytosis of postprandial triglyceride-rich lipoproteins - Fischer, Alexander W. (Mol Metab, 2018)
OBJECTIVE: Insulin resistance is associated with impaired receptor dependent hepatic uptake of triglyceride-rich lipoproteins (TRL), promoting hypertriglyceridemia and atherosclerosis. Next to low-density lipoprotein (LDL) receptor (LDLR) and syndecan-1, the LDLR-related protein 1 (LRP1) stimulated by insulin action contributes to the rapid clearance of TRL in the postprandial state. Here, we investigated the hypothesis that the adaptor protein phosphotyrosine interacting domain-containing protein 1 (PID1) regulates LRP1 function, thereby controlling hepatic endocytosis of postprandial lipoproteins. METHODS: Localization and interaction of PID1 and LRP1 in cultured hepatocytes was studied by confocal microscopy of fluorescent tagged proteins, by indirect immunohistochemistry of endogenous proteins, by GST-based pull down and by immunoprecipitation experiments. The in vivo relevance of PID1 was assessed using whole body as well as liver-specific Pid1-deficient mice on a wild type or Ldlr-deficient (Ldlr(−/−)) background. Intravital microscopy was used to study LRP1 translocation in the liver. Lipoprotein metabolism was investigated by lipoprotein profiling, gene and protein expression as well as organ-specific uptake of radiolabelled TRL. RESULTS: PID1 co-localized in perinuclear endosomes and was found associated with LRP1 under fasting conditions. We identified the distal NPxY motif of the intracellular C-terminal domain (ICD) of LRP1 as the site critical for the interaction with PID1. Insulin-mediated NPxY-phosphorylation caused the dissociation of PID1 from the ICD, causing LRP1 translocation to the plasma membrane. PID1 deletion resulted in higher LRP1 abundance at the cell surface, higher LDLR protein levels and, paradoxically, reduced total LRP1. The latter can be explained by higher receptor shedding, which we observed in cultured Pid1-deficient hepatocytes. Consistently, PID1 deficiency alone led to increased LDLR-dependent endocytosis of postprandial lipoproteins and lower plasma triglycerides. In contrast, hepatic PID1 deletion on an Ldlr(−/−) background reduced lipoprotein uptake into liver and caused plasma TRL accumulation. CONCLUSIONS: By acting as an insulin-dependent retention adaptor, PID1 serves as a regulator of LRP1 function controlling the disposal of postprandial lipoproteins. PID1 inhibition provides a novel approach to lower plasma levels of pro-atherogenic TRL remnants by stimulating endocytic function of both LRP1 and LDLR in the liver.